Dynamic Changes of the Anthocyanin Biosynthesis Mechanism During the Development of Heading Chinese Cabbage (Brassica rapa L.) and Arabidopsis Under the Control of BrMYB2 - He, Qiong; Lu, Qianqian; He, Yuting; Wang, Yaxiu; Zhang, Ninan; Zhao, Wenbin; Zhang, Lugang (Frontiers in Plant Science, 2020)
Chinese cabbage is an important vegetable mainly planted in Asian countries, and mining the molecular mechanism responsible for purple coloration in Brassica crops is fast becoming a research hotspot. In particular, the anthocyanin accumulation characteristic of purple heading Chinese cabbage, along with the plant’s growth and head developing, is still largely unknown. To elucidate the dynamic anthocyanin biosynthesis mechanism of Chinese cabbage during its development processes, here we investigated the expression profiles of 86 anthocyanin biosynthesis genes and corresponding anthocyanin accumulation characteristics of plants as they grew and their heads developed, between purple heading Chinese cabbage 11S91 and its breeding parents. Anthocyanin accumulation of 11S91 increased from the early head formation period onward, whereas the purple trait donor 95T2-5 constantly accumulated anthocyanin throughout its whole plant development. Increasing expression levels of BrMYB2 and BrTT8 together with the downregulation of BrMYBL2.1, BrMYBL2.2, and BrLBD39.1 occurred in both 11S91 and 95T2-5 plants during their growth, accompanied by the significantly continuous upregulation of a phenylpropanoid metabolic gene, BrPAL3.1; a series of early biosynthesis genes, such as BrCHSs, BrCHIs, BrF3Hs, and BrF3’H; as well as some key late biosynthesis genes, such as BrDFR1, BrANS1, BrUF3GT2, BrUF5GT, Br5MAT, and Brp-Cout; in addition to the transport genes BrGST1 and BrGST2. Dynamic expression profiles of these upregulated genes correlated well with the total anthocyanin contents during the processes of plant growth and leaf head development, and results supported by similar evidence for structural genes were also found in the BrMYB2 transgenic Arabidopsis. After intersubspecific hybridization breeding, the purple interior heading leaves of 11S91 inherited the partial purple phenotypes from 95T2-5 while the phenotypes of seedlings and heads were mainly acquired from white 94S17; comparatively in expression patterns of investigated anthocyanin biosynthesis genes, cotyledons of 11S91 might inherit the majority of genetic information from the white type parent, whereas the growth seedlings and developing heading tissues of 11S91 featured expression patterns of these genes more similar to 95T2-5. This comprehensive set of results provides new evidence for a better understanding of the anthocyanin biosynthesis mechanism and future breeding of new purple Brassica vegetables.